Stimulus‐Triggered Formation of an Anion–Cation Exciplex in Copper(I) Complexes as a Mechanism for Mechanochromic Phosphorescence. Issue 41 (12th September 2018) - Hupp, Benjamin; Nitsch, Jörn; Schmitt, Tanja; Bertermann, Rüdiger; Edkins, Katharina; Hirsch, Florian; Fischer, Ingo; Auth, Michael; Sperlich, Andreas; Steffen, Andreas
Abstract: The investigation of the mechanisms of mechanochromic luminescence is of fundamental importance for the development of materials for photonic sensors, data storage, and luminescence switches. The structural origin of this phenomenon in phosphorescent molecular systems is rarely known and thus the formulation of structure–property relationships remains challenging. Changes in the M–M interactions have been proposed as the main mechanism with d 10 coinage metal compounds. Herein, we describe a new mechanism—a mechanically induced reversible formation of a cation–anion exciplex based on Cu–F interactions—that leads to highly efficient mechanochromic phosphorescence and unusual large emission shifts from UV‐blue to yellow for Cu I complexes. The low‐energy luminescence is thermo‐ and vaporesponsive, thus allowing the generation of white light as well as for recovering the original UV‐blue emission. Abstract : Grind 'n' glow : Highly efficient mechanochromic, vapochromic, and thermochromic phosphorescence is observed in ionic dicopper(I) complexes through a stimulus‐triggered formation of an exciplex. Grinding leads to changes in the cation–anion distances and to the formation of Cu–F interactions in the triplet excited state.